Drift of a Drowning Victim in Rivers: Conceptualization and Global Sensitivity Analysis Under Idealized Flow Conditions - C. Delhez; N. Rivière; S. Erpicum; M. Pirotton; P. Archambeau; M. Arnst; J. Bierens; B. Dewals (Water Resources Research, 2023)
Abstract We present a conceptual model of the drift of a drowning victim in a river, accounting for the mechanical effects of body decomposition. The model was tested under idealized flow conditions (uniform flow) and a global sensitivity analysis was performed. Uncertainties in body morphology, flow‐body interaction parameters (e.g., drag coefficient) and drowning characteristics were considered. The results emphasize the importance of predicting the body vertical position since it considerably influences the streamwise body drift velocity, due to the significant difference between near‐surface and near‐bed velocity. The results also highlight the value of testimonies providing information on body mass and height, as decreasing uncertainty on these input data strongly reduces uncertainties on the predicted body streamwise position. Next step of the research will consist in coupling the model with an Eulerian multi‐dimensional model of river hydrodynamics.